2016
DOI: 10.1016/j.otsr.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Small femoral offset is a risk factor for lateral femoral cutaneous nerve injury during total hip arthroplasty using a direct anterior approach

Abstract: IV, retrospective historical cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…The LFCN of the two patients had three branches at the end, and the lateral branch passed the TFL. In the control group, 15 (24.2%) patients described abnormal symptoms in the anterolateral thigh, including numbness (15), dull sensation (15), and tingling or pain (4) in the 1st month follow-up, which was signi cantly higher than that in the ultrasound group. The area of abnormal symptoms of the control group was 133.1 ± 104.9 (49 ~ 375) cm 2 , which was signi cant larger than that of ultrasound guiding group.…”
Section: Statisticsmentioning
confidence: 87%
See 1 more Smart Citation
“…The LFCN of the two patients had three branches at the end, and the lateral branch passed the TFL. In the control group, 15 (24.2%) patients described abnormal symptoms in the anterolateral thigh, including numbness (15), dull sensation (15), and tingling or pain (4) in the 1st month follow-up, which was signi cantly higher than that in the ultrasound group. The area of abnormal symptoms of the control group was 133.1 ± 104.9 (49 ~ 375) cm 2 , which was signi cant larger than that of ultrasound guiding group.…”
Section: Statisticsmentioning
confidence: 87%
“…Some studies from the clinic or cadaveric hips reported that the rate of LFCN injury was 3.29%-81.00% [10,11,13,14]. This huge gap between different studies may be partially caused by surgical technique, including nerve stretching, compression, laceration, and suturing; however, the high anatomical variant rate of LFCN distribution and femoral offset, was at a higher risk for surgical injury [15][16][17]. The LFCN, derived from the lumbar nerve 2-3, crosses the iliacus obliquely, and then runs toward the anterior superior iliac spine (ASIS).…”
Section: Introductionmentioning
confidence: 99%
“…The stem comes in 12 sizes [1][2][3][4][5][6][7][8][9][10][11]14 and a 12 to 14 mm cone. The stem sizes are offered in two offset types: standard and lateral.…”
Section: Surgerymentioning
confidence: 99%
“…An under-correction of the FO will lead to a weakness in the abductor muscles, resulting in a disturbed gait pattern and a high risk of dislocation, whereas an overcorrection will provide an increased tension on the soft tissues surrounding the hip, which can lead to postoperative pain and trochanteric bursitis. 5,6 Ozaki et al 7 described that a small FO causes a significant risk for the lateral femoral cutaneous nerve injury following THA with DAA. As DAA is becoming an increasingly popular approach for THA, it is important to know the risks when applying this technique and the importance of the FO.…”
mentioning
confidence: 99%
“…Some studies from the clinic or cadaveric hips reported that the rate of LFCN injury was 3.29%-81.00% [10,11,13,14]. This huge gap between different studies may be partially caused by surgical technique, including nerve stretching, compression, laceration, and suturing; however, the high anatomical variant rate of LFCN distribution and femoral offset, was at a higher risk for surgical injury [15][16][17]. The LFCN, derived from the lumbar nerve 2-3, crosses the iliacus obliquely, and then runs toward the anterior superior iliac spine (ASIS).…”
Section: Introductionmentioning
confidence: 99%